Inhalation Administration of the Sesquiterpenoid Aristolen-1(10)-en-9-ol from Nardostachys chinensis Has a Sedative Effect via the GABAergic System - Takemoto, Hiroaki; Ito, Michiho; Asada, Yoshihisa; Kobayashi, Yoshinori (Planta Medica, 2015)
Spikenard, the dried roots of Nardostachys chinensis, contains sesquiterpenoids and is widely used as an herbal tranquilizer. We previously demonstrated that spikenard vapor showed a sedative effect when administered by inhalation, and we identified hydrocarbon sesquiterpenoids as active components. Here we investigated the other components that contribute to the effects of spikenard. Six oxygenated sesquiterpenoids, including aristolane- and guaiane-types, were isolated from an acetone extract of spikenard. We evaluated the sedative activities of these oxygenated compounds using an inhalation administration method in a caffeine-treated excitatory mouse model. We identified aristolen-1(10)-en-9-ol and patchouli alcohol as highly effective sedative components. These compounds inhibited locomotion in mice by approximately 60 % at a dose of 300 µg/cage. In addition, aristolen-1(10)-en-9-ol prolonged pentobarbital-induced sleep to the same extent as 1 mg/kg diazepam. This effect completely disappeared with the administration of the GABAA-benzodiazepine receptor antagonist flumazenil (3 mg/kg), suggesting that the sedative effect of aristolen-1(10)-en-9-ol is expressed via the GABAergic system. Furthermore, differently from diazepam, inhalation of aristolen-1(10)-en-9-ol for 1 h did not affect the motor coordination in the rota-rod test. In the present study, we identified active components and provided evidence supporting the traditional sedative use of spikenard. Our research suggests that aristolen-1(10)-en-9-ol may be an effective aromatherapy, providing mild sedation.
Keywords: Nardostachys chinensis; Valerianaceae; aristolen-1(10)-en-9-ol; inhalation administration; sedation; GABAergic system